Influenza A Pneumonia Associated with Diffuse Alveolar Hemorrhage. A Case Report and Literature Review - Toolsie, Omesh (Am J Case Rep, 2019)
Patient: Female, 80 Final Diagnosis: Diffuse alveolar hemorrhage in influenza A viral pneumonia Symptoms: Generalized fatigue • shortness of breath Medication: — Clinical Procedure: — Specialty: Critical Care Medicine OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: Diffuse alveolar hemorrhage (DAH) represents a life-threatening complication for many respiratory infections. We present a case of a patient with influenza A pneumonia associated with DAH. CASE REPORT: An 80-year-old female patient was admitted with lethargy, dyspnea, and chest pain. On examination, she was afebrile with bilateral basal inspiratory crackles. Her chest x-ray revealed retro-cardiac infiltrate. Her hospital course was complicated by respiratory failure and septic shock requiring intubation. Nasopharyngeal swabs, rapid testing was positive for influenza A. Bronchoscopy showed diffuse bleeding and bronchoalveolar lavage (BAL) of the left lower lobe showed progressively bloody returns, consistent with DAH. Methylprednisolone 250 mg daily was started, with improvement in oxygenation. Repeat bronchoscopy 2 days later revealed normal mucosa and no further bleeding. The patient’s respiratory status and infiltrates improved, but her overall status continued to deteriorate, and she died 2 weeks after admission. CONCLUSIONS: High fatality rates have been reported in patients with influenza A viral pneumonia complicated by DAH. Advanced age and the presence of significant co-morbidities might predispose a patient to the development of a more aggressive clinical manifestation of influenza A and also increases the risk of developing DAH. Therefore, clinicians managing patients with influenza A viral pneumonia with this predisposing history should also maintain a high suspicion for DAH. We suggest early BAL for diagnosis and for the evaluation of other infections etiologies. Aggressive supportive care and the use of antiviral agents is recommended. The role of steroids is unclear and can be considered in patients with fulminant disease but might have no outcome benefit.